Bioactive Synthetic Polymer-Based Polyelectrolyte LbL Coating Assembly on Surface Treated AZ31-Mg Alloys - Sangeetha Kunjukunju; Abhijit Roy; John Ohodnicki; Boeun Lee; Joe E. Candiello; Mitali Patil; Prashant N. Kumta (Journal of Functional Biomaterials, 2023)
Polyelectrolyte layer-by-layer (LbL) films on pretreated Mg containing 3 wt.% Al and 1 wt.% Zn (MgAZ31) alloy surfaces were prepared under physiological conditions offering improved bioresponse and corrosive protection. Pretreatments of the model MgAZ31 substrate surfaces were performed by alkaline and fluoride coating methods. The anti-corrosion and cytocompatibility behavior of pretreated substrates were evaluated. The LbL film assembly consisted of an initial layer of polyethyleneimine (PEI), followed by alternate layers of poly (lactic-co-glycolic acid) (PLGA) and poly (allylamine hydrochloride) (PAH), which self-arrange via electrostatic interactions on the pretreated MgAZ31 alloy substrate surface. The physicochemical characterization, surface morphologies, and microstructures of the LbL films were investigated using Fourier-transformed infrared spectroscopy (FTIR), atomic force microscopy (AFM), X-ray diffraction (XRD), and scanning electron microscopy (SEM). The in vitro stability studies related to the LbL coatings confirmed that the surface treatments are imperative to achieve the lasting stability of PLGA/PAH layers. Electrochemical impedance spectroscopy measurements demonstrated that pretreated and LbL multilayered coated substrates enhanced the corrosion resistance of the bare MgAZ31 alloy. Cytocompatibility studies using human mesenchymal stem cells seeded directly over the substrates showed that the pretreated and LbL-generated surfaces were more cytocompatible, displaying reduced cytotoxicity than the bare MgAZ31. The release of bovine serum albumin protein from the LbL films was also studied. The initial data presented cooperatively demonstrate the promise of creating LbL layers on Mg-related bioresorbable scaffolds to obtain improved surface bio-related activity.